O Aprendizado do alemão-padrão por alunos bilíngües: pesquisas e ações - Spinassé, Karen Pupp (Contingentia, 2009)
This paper aims to contribute to the rich discussion that has been developed in this journal throughout previous editions. Many authors have already written here about their considerations and praxis regarding bilingualism, bilingual contexts and bilingual education from different perspectives. Thus, this paper also brings to discussion aspects of the education in bilingual settings in Brazil, where people speak Portuguese and a variety of German basis called Hunsrückisch as their mother tongue. Moreover, this paper aims to be an account of results from different researches, which deal with the advantages of speaking dialect to learn standard German and the prejudices, learners coming from minority languages confront.